Concern for the patient's experience comes of age - Irwin Press (The Beryl Institute, 2014)
In this special guest editorial for the inaugural issue of Patient Experience Journal. Dr. Press reflects on how the focus on patient experience has evolved. He starts with a reflection, "A journal devoted exclusively to the patient's experience? A patient satisfaction survey mandated by CMS for all hospitals and a portion of reimbursement dependent upon the scores? An Institute and an "Association" addressing Patient Experience? A new hospital administrative position labeled "Chief Experience Officer"? Some 30 years ago no one would have predicted any of these." Dr. Press helps us explore and review how the patient experience movement has evolved and the implications of both our history and current state on how we address patient and family needs moving forward. He aptly offers in closing, "Concern for the patient's experience is coming of age."